The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1105/tpc.010611
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 Proteins Are Constituents of the Insoluble Glycoprotein Framework of the Chlamydomonas Cell Wall

Abstract: The cell wall of the unicellular green alga Chlamydomonas reinhardtii consists predominantly of Hyp-rich glycoproteins, which also occur in the extracellular matrix of multicellular green algae and higher plants. In addition to the Hyp-rich polypeptides, the insoluble glycoprotein framework of the Chlamydomonas cell wall contains minor amounts of 14-3-3 proteins, as revealed by immunochemical studies and mass spectroscopic analysis of tryptic peptides. Polypeptides immunologically related to the 14-3-3 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 74 publications
5
55
0
2
Order By: Relevance
“…Its HRGP constituents are, however, not yet characterized. Previous pulse-labeling and pulse-chase experiments and immunochemical studies indicated that the chaotrope-soluble cell wall fraction contains soluble precursors of the insoluble Chlamydomonas wall fraction (38,41,42). In this study, we provide evidence that the chaotrope-soluble HRGP GP2 is such a precursor of the insoluble glycoprotein framework of the Chlamydomonas cell wall.…”
supporting
confidence: 50%
See 4 more Smart Citations
“…Its HRGP constituents are, however, not yet characterized. Previous pulse-labeling and pulse-chase experiments and immunochemical studies indicated that the chaotrope-soluble cell wall fraction contains soluble precursors of the insoluble Chlamydomonas wall fraction (38,41,42). In this study, we provide evidence that the chaotrope-soluble HRGP GP2 is such a precursor of the insoluble glycoprotein framework of the Chlamydomonas cell wall.…”
supporting
confidence: 50%
“…The 64-and 45-kDa components released from the insoluble cell wall fraction by chemical deglycosylation are not individual polypeptides as reported previously (38). Edman degradation of these particular constituents of the insoluble wall fraction revealed that their N-terminal amino acid sequences are rather heterogeneous (38).…”
Section: Characterization Of the Insoluble Cell Wall Fraction Of Cmentioning
confidence: 65%
See 3 more Smart Citations